1985
DOI: 10.1111/j.1432-1033.1985.tb08851.x
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and processing of liposomal phospholipids by Kupffer cells in vitro

Abstract: We investigated the intracellular metabolic fate of choline-labeled phosphatidylcholines and sphingomyelin taken up by rat Kupffer cells in maintenance culture during interaction with large unilamellar liposomes composed of cholesterol, labeled choline-phospholipid and phosphatidylserine (molar ration 5 : 4 : 1).With both labeled compounds only small proportions of water-soluble radioactivity were found to accumulate in the cells and in the culture medium, suggesting limited phospholipid degradation. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
2

Year Published

1986
1986
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 44 publications
(32 reference statements)
1
20
2
Order By: Relevance
“…Liposomes are preferentially trapped by phagocytic cells in the reticuloendothelial organs such as the liver and spleen (3,9,10). However, in this study we observed no such greater distribution of Lip-RFP than of free RFP in the liver, although some prolonged retention of Lip-RFP in the spleen was noted.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Liposomes are preferentially trapped by phagocytic cells in the reticuloendothelial organs such as the liver and spleen (3,9,10). However, in this study we observed no such greater distribution of Lip-RFP than of free RFP in the liver, although some prolonged retention of Lip-RFP in the spleen was noted.…”
Section: Discussioncontrasting
confidence: 53%
“…Since liposomes are preferentially taken up by reticuloendothelial cells (3,9,10), liposomal encapsulation of a given agent should result in greater availability of the agent to parasites present in phagocytic cells. The entrapment of certain antibiotics in liposomes increases their activity against bacteria phagocytosed into macrophages in in vitro culture systems (3,5,7).…”
mentioning
confidence: 99%
“…On the other hand, we did not directly examine the disposition of the DPPC, DHSG, PEG-DSPE, and H12-PEG-Glu2C18 in H12-(ADP)-liposomes. Previous reports have shown that the phospholipids in liposomes are metabolized in the MPS and reused as cell membranes or are excreted into the bile (Dijkstra et al, 1985;Verkade et al, 1991). Therefore, it is also possible that phospholipids in H12-(ADP)-liposome are also metabolized and excreted in the same manner as the other liposome components, as mentioned above.…”
mentioning
confidence: 80%
“…It is also well known from results of other in vitro studies that macrophages can take up liposomes very avidly (8,21,23,27). Uptake occurs predominantly by way of phagocytosis, followed by extensive degradation of the vesicles within the lysosomal compartment of the cells (9,24 (14). In contrast to the effect of 50 or 150 ,ug of free ampicillin per ml plus empty liposomes, a concentration of 50 ,g of free ampicillin plus 100 ,ug of liposome-entrapped ampicillin per ml killed 99% of the intracellular bacteria.…”
Section: Discussionmentioning
confidence: 99%